Buzzkill ebook - Cates, Donny (Buzzkill (2013)., 2018)
Ruben is an unconventional superhero who gets his powers through the consumption of alcohol and illicit drugs. On one fateful day, facing a world-ending threat, Reuben drank so much that he blacked out. He saved the world...but he has no idea how or why. Now, he's in recovery, trying to get sober and piece together not only the events of the night in question, but the broken parts of his life as an alcoholic and an addict. Now back in print from Image Comics, BUZZKILL is a critically acclaimed miniseries from the creative team that brought you GOD COUNTRY and The Paybacks, and the writer of REDNECK, Babyteeth, Ghost Fleet, and more. Collects BUZZKILL #1-4. Author: Donny Cates, Mark Reznicek. Illustrator: Geoff Shaw, Lauren Affe . 2017 Mark Reznicek and Donny Cates.